DO POLICY REGIMES MATTER? THE INTERDEPENDENCE OF BITCOIN WITH EQUITIES, GOLD, AND USD/INR IN INDIA - Bulut, Emre (Anadolu Üniversitesi, 2026)
This study investigates state-contingent linkages. This is done using the multivariate quantile-on-quantile framework. The dataset employed is daily data. The span of the data is from 1 January 2018 to 13 July 2023. The linkages examined are between Bitcoin (BTC/USD) and three domestic risk factors. These factors include Indian equities (NIFTY-100), gold (XAU/USD), and the rupee-dollar exchange rate (USD/INR). The analysis maps dependence surfaces β(θ,Φ) or the analysis examines BTC with respect to each predictor. It also evaluates how the linkages adjust across five specific Indian policy windows. These periods are defined by key events. The windows investigated are: the RBI banking restriction, the post-Supreme Court/pre-tax interval, the VDA tax, the TDS phase, and the post-FTX period. Full-sample results indicate modest comovement near the joint median but pronounced tail effects: BTC-equity linkages strengthen during equity drawdowns; BTC-gold dependence turns positive in gold’s upper quantiles; and BTC’s association with USD/INR intensifies under rupee depreciation. Regime-difference panels show selective reweighting across transitions, dampening center-region links while preserving or amplifying tail sensitivities. Findings remain robust under reasonable tuning choices. The evidence supports state-contingent portfolio management and motivates macroprudential monitoring of crypto-FX channels.
Keywords: Bitcoin; Quantile-on-Quantile Regression; State-Contingent Dependence; Tail Risk; Regime Shifts